1985
DOI: 10.1002/1097-0142(19850115)55:2<400::aid-cncr2820550218>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid carcinoma arising in an intraparotid lymph node

Abstract: A well‐differentiated mucoepidermoid carcinoma that was confined to, and apparently arose within, an intraparotid lymph node is reported. Salivary gland ducts and acini often are found within intraparotid lymph nodes, and occasionally within extraparotid nodes. Salivary gland tumors, both benign and malignant, can develop within this ectopic salivary tissue. When a malignant salivary‐gland‐type neoplasm is found within an intraparotid or periparotid lymph node, the possibility exists that the tumor has arisen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In 1985, Smith et al [ 1 ] reported a rare, and rather interesting, case of MEC arising in an intraparotid lymph node. They described a 42-year-old, Hispanic male who presented complaining of a mass in the left parotid region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 1985, Smith et al [ 1 ] reported a rare, and rather interesting, case of MEC arising in an intraparotid lymph node. They described a 42-year-old, Hispanic male who presented complaining of a mass in the left parotid region.…”
Section: Discussionmentioning
confidence: 99%
“…After superficial parotidectomy, the microscopic examination revealed a low-grade MEC confined entirely to the lymph node, with normal surrounding parotid tissue. The postoperative period was uneventful and one-year follow-up revealed no recurrence of the disease [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations